EDUCATIONAL INNOVATIONS: AXIOLOGICAL BASES OF MEGALOPOLIS YOUTH'S READINESS - Olga V. Kruzhkova; Irina V. Vorobyeva (Russian State Vocational Pedagogical University, 2015)
The purpose of the present article is to examine the value bases of the readiness for innovations in the modern education of the youth of the megalopolises.Methods. As the methods were used: theoretical analysis and modeling method, as well as a survey of students of megalopolises (n = 1187) by the valuable questionnaire of S. Schwartz.Results. The authors give the description of educational innovations from the perspective of the overall needs of society in an individual which has technological skills and targets in acquiring and operating information. The reorientation of education on advancing development is implemented through numerous tactical and strategic changes in its form, content, methods and structure of the educational system in general. These changes can be united into five groups. Organizational innovations are pointed at changing the structure of education in accordance with the dynamic characteristics of society. Informative innovations suggest differentiation of activities and the level of responsibility of professionals in the same profile. The activity innovations are focused on changing the teachers' readiness to transform their professional work and the development of their innovative competence. Productive innovations solve the problem of personality development of a professional in accordance with the social mandate. Socio-control innovations are designed to achieve transparency of management education for society. Implementation of the considered innovations is provided by numerous factors, which includes readiness of students to participate in the latest developments of the educational environment. The basis of this readiness contains value orientations, actualizing expectations and targets of young people as participants of innovations. Value priorities of megalopolis youth are highlighted: independence of thoughts and actions, hedonism, reputation and goodwill. On the one hand, these values provide a high readiness of young people to participate in educational innovation, but on the other, reflect their passive consumer attitudes towards innovation.Scientific novelty. The relation to introduction of innovations for today is underexplored. Authors of the publication have tried to close the gaps in this socially significant question.Practical significance. The obtained data can be used for organisation of innovation activities on education development and involving the most up-and-coming students as participants and creators.